'I thought they were going to handle me like a queen but they didn't': A qualitative study exploring the quality of care provided to women at the time of birth. (July 2018) - Lambert, Jaki; Etsane, Elsie; Bergh, Anne-Marie; Pattinson, Robert; van den Broek, Nynke
Highlights: Women's experiences of birth show that 'caring' by healthcare providers is at least as important as 'competence'. Without supportive leadership to create a caring environment, training in respectful care may not change practice. It is important that women who attend for care as well as healthcare providers are clear about the structural and institutional barriers to providing a better quality of care and who is responsible for addressing these. Using mobile phones to provide feedback is acceptable to women and healthcare providers. Abstract: Objective: To explore experiences of care during labour and birth from the perspectives of both the healthcare provider and women receiving care, to inform recommendations for how the quality of care can be improved and monitored, and, to identify the main aspects of care that are important to women. Design: A descriptive phenomenological approach. 53 interviews and 10KII as pertable 1 took place including in-depth interviews (IDI), focus group discussions (FGD) and key informant interviews (KII) conducted with women, healthcare providers, managers and policy makers. Following verbatim transcription thematic framework analysis was used to describe the lived experience of those interviewed. Setting: 11 public healthcare facilities providing maternity care in urban Tshwane District, Gauteng Province ( n  = 4) and rural Waterberg District, Limpopo Province ( n  = 7), South Africa. Participants: Women who had given birth in the preceding 12 weeks (49 women, 7 FGD and 23 IDI); healthcare providers working in the labour wards (33 healthcare providers; nurses, midwives, medical staff, 5 FGD, 18 IDI; managers and policy makers (10 KII). Findings: Both women and healthcare providers largely feel alone and unsupported. There is mutual distrust between women and healthcare providers exacerbated by word of mouth and the media. A lack of belief in women's ability to make appropriate choices negates principles of choice and consent. Procedure- rather than patient-centred care is prioritised by healthcare providers. Although healthcare providers know the principles of good quality care, this was not reflected in the care women described as having received. Beliefs and attitudes as well as structural and organisational problems make it difficult to provide good quality care. Caring behaviour and environment as well as companionship are the most important needs highlighted by women. Professional hierarchy is rarely seen as supportive by healthcare providers but when present, good leadership changes the culture and experience of women and care providers. The use of mobile phones to provide feedback regarding care was positively viewed by women. Conclusion: Clarity regarding what a healthcare facility can (or cannot provide) is important in order to separate practice issues from structural and organisational constraints. Improvements in quality that focus on caring as well as competence should be prioritised. Increased dialogue between healthcare providers and users should be encouraged and prioritised. Implications for practice: A renewed focus is needed to ensure companionship during labour and birth is facilitated. Training in respectful maternity care needs to prioritise caring behaviour and supportive leadership.